Chirality assignment of single-walled carbon nanotubes with strain. - Li, L; Nicholas, R; Deacon, R; Shields, P (2004)
Strain-induced band gap shifts that depend strongly on the chiral angle have been observed by optical spectroscopy in single-walled carbon nanotubes (SWCNTs). Uniaxial and torsional strains are generated by changing the environment surrounding the SWCNTs, using the surrounding D2O ice temperature or the hydration state of a wrapping polymer. These methods are used as diagnostic tools to determine the quantum number q and examine chiral vector indices for specific nanotubes.